“What about building 7?” A social psychological study of online discussion of 9/11 conspiracy theories - Wood, Michael J.; Douglas, Karen M. (Frontiers in Psychology, 2013)
Recent research into the psychology of conspiracy belief has highlighted the importance of belief systems in the acceptance or rejection of conspiracy theories. We examined a large sample of conspiracist (pro-conspiracy-theory) and conventionalist (anti-conspiracy-theory) comments on news websites in order to investigate the relative importance of promoting alternative explanations versus rejecting conventional explanations for events. In accordance with our hypotheses, we found that conspiracist commenters were more likely to argue against the opposing interpretation and less likely to argue in favor of their own interpretation, while the opposite was true of conventionalist commenters. However, conspiracist comments were more likely to explicitly put forward an account than conventionalist comments were. In addition, conspiracists were more likely to express mistrust and made more positive and fewer negative references to other conspiracy theories. The data also indicate that conspiracists were largely unwilling to apply the “conspiracy theory” label to their own beliefs and objected when others did so, lending support to the long-held suggestion that conspiracy belief carries a social stigma. Finally, conventionalist arguments tended to have a more hostile tone. These tendencies in persuasive communication can be understood as a reflection of an underlying conspiracist worldview in which the details of individual conspiracy theories are less important than a generalized rejection of official explanations.